2004
DOI: 10.2176/nmc.44.105
|View full text |Cite
|
Sign up to set email alerts
|

Supratentorial Dynamic Computed Tomography for the Diagnosis of Vertebrobasilar Ischemic Stroke

Abstract: Dynamic computed tomography (CT) is an established method for the evaluation of perfusion in acute ischemic stroke, but is not frequently used to assess infratentorial ischemia. Eleven patients with vertebrobasilar ischemia underwent dynamic CT on admission and/or during the followup period. The time of appearance (TA) and time to peak (TTP) were mapped and differences in TA (DTA) and TTP (DTTP) between the bilateral middle cerebral artery and posterior cerebral artery (PCA) territories were calculated. Conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…19,20 We have recently demonstrated that CTA-SIs increase the sensitivity for early ischemic changes in the posterior circulation compared with noncontrast CT. 12,16 Compared with CTA-SI, perfusion CT techniques may provide additional diagnostic and prognostic information in patients with acute posterior circulation stroke. 21,22 The comparison of CTA, perfusion CT, and multimodal MRI to predict functional outcome and treatment response in patients with BAO could be the subject of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 We have recently demonstrated that CTA-SIs increase the sensitivity for early ischemic changes in the posterior circulation compared with noncontrast CT. 12,16 Compared with CTA-SI, perfusion CT techniques may provide additional diagnostic and prognostic information in patients with acute posterior circulation stroke. 21,22 The comparison of CTA, perfusion CT, and multimodal MRI to predict functional outcome and treatment response in patients with BAO could be the subject of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The MR-angiographic view of the cervical vessels is very similar to the CT-angiographic one D30 present, PCT has demonstrated 95% accuracy in the delineation of the extent of supratentorial strokes, despite its limited spatial coverage [24]. PCT has also been demonstrated as useful in the evaluation of vertebro-basilar ischemia [25].…”
Section: Fig 1 Amentioning
confidence: 99%
“…In addition, to evaluate posterior circulation ischemia, protocols must be appropriately adjusted to include lower sections (Fig 7). 9 Nagahori et al 45 demonstrated prolonged time of bolus arrival and TTP in posterior circulation infarcts. CTP may be a potentially useful adjunct, particularly in the evaluation of posterior fossa ischemia because this location is notoriously difficult to evaluate on NCCT.…”
Section: Section Selectionmentioning
confidence: 99%